A Review of the Effect of Management Practices on Campylobacter Prevalence in Poultry Farms - Sibanda, Nompilo; McKenna, Aaron; Richmond, Anne; Ricke, Steven C.; Callaway, Todd; Stratakos, Alexandros Ch.; Gundogdu, Ozan; Corcionivoschi, Nicolae (Frontiers in Microbiology, 2018)
Poultry is frequently associated with campylobacteriosis in humans, with Campylobacter jejuni being the most common of the Campylobacter associated with human cases. Extensive research on Campylobacter has been done over the last two decades. This has resulted in interventions being put in place on farms and in processing plants. Despite these interventions, coupled with increased media coverage to educate the consumer on Campylobacter prevalence and campylobacteriosis, human health incidents are still high. Recent research is now shifting towards further understanding of the microorganisms to challenge interventions in place and to look at further and more relevant interventions for the reduction in human incidents. Farm practices play a key role in the control of colonisation within poultry houses and among flocks. Prevalence at the farm level can be up to 100% and time of colonisation may vary widely between flocks. Considerable research has been performed to understand how farm management and animal health practices can affect colonisation on farms. This review will focus on farm practices to date as a baseline for future interventions as the microorganism becomes better understood. Further research is required to understand the chicken microbiome and factors influencing vertical transmission. The persistence of Campylobacter in animal and environmental reservoirs within and around farms requires further investigation to tailor farm practices towards preventing such reservoirs.